Genome-Wide Identification and Expression Analysis of the ALDH Gene Family in Sinonovacula constricta Bivalve in Response to Acute Hypersaline Stress - Jianing Yu; Biao Wu; Yinghui Dong; Zhihua Lin; Hanhan Yao (Animals)
The razor clam Sinonovacula constricta, a significant marine bivalve species, inhabits estuaries and encounters salinity stress. Despite its commercial importance, there is limited understanding of its adaptive mechanisms to high salinity. Aldehyde dehydrogenases (ALDHs), which belong to the NAD(P)+-dependent superfamily, play a crucial role in stress resilience by participating in catabolic and anabolic pathways, such as carnitine synthesis, glycolysis, and amino acid metabolism. This study presents the first comprehensive analysis of the ALDH family in S. constricta under acute high salt stress conditions and identifies 16 ScALDH genes across 10 subfamilies. These genes are located on eight chromosomes, with tandem duplications observed on chromosome 10; they encode mostly acidic and hydrophilic proteins. Among them, ScALDH18A1 contains a conserved P5CS domain that is implicated in proline synthesis and osmotic regulation. The expression of 14 ScALDH members were significantly altered under acute salt stress conditions, with ScALDH8 and ScALDH18A1 showing increased expression levels, suggesting their involvement in osmotic pressure regulation. This research provides insights into the characteristics, evolution, and response to salinity stress of the ScALDH gene family while shedding light on ALDH function in bivalves, as well as serving as a foundation for further studies on osmotic stress regulation.